Comparison of McKeown Minimally Invasive Esophagectomy vs sweet esophagectomy for esophageal squamous cell carcinoma: A retrospective study - Yu, Fan; Zhang, Yaozhong; Xu, Haidi; Li, Kuankuan; Gheng, Jingge; Lin, Chenxi; Li, Lei; Wang, Na; Wang, Lei (Frontiers in Oncology, 2022)
The McKeown minimally invasive esophagectomy(MIE) and Sweet Esophagectomy are the two most widely used transthoracic esophagectomy techniques. We evaluated and compared the therapeutic efficacy of these two approaches to determine the appropriate method to treat middle or lower third esophageal carcinomas, after neoadjuvant chemotherapy combined with immunotherapy (NACI). We retrospectively reviewed patients who received NACI and underwent esophagectomy with the Sweet Esophagectomy (n= 43) and McKeown MIE (n=167) at the Fourth Hospital of Hebei Medical University between December 2019 and May 2022. Perioperative-related indicators and disease-free survival rates were compared between groups. This retrospective observational study showed that Sweet esophagectomy and McKeown MIE after NACI therapy for resectable ESCC patients appeared to be safe with low operative mortality and morbidity rate in the current population. In addition, Sweet esophagectmy was associated with a lower rate of severe complications and shorter hospital length of stay, for over 70 years old patients, compared with the McKeown MIE. No differences were observed in intensive care unit length of stay, mortality and morbidity rate. The Sweet approach has advantage in hospital stay for the treatment of the elderly NACI patients with middle or lower third esophageal carcinomas. Both Sweet esophagectomy and McKeown MIE are safe, effective, and worthwhile approaches in modern thoracic surgery.